USING MIXED GAMMA AND ULTRAVIOLET RADIATION FOR DISINFESTIATION OF IRAQI DATES FRUIT FROM EPHESTIA CAUTELLA - & Mahdi, Saad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Fig moth E. cautella, considered the most serious pests infest dates and cause economic losses in the field and warehouses in Iraq which produces between 600-700 thousand tons of dates annually. In order to reduce this damage, different pest control methods are used, and mixed radiation considered one of the newest and innovative way to control the Moth that attack stored dates. This research has been done in Nuclear Laboratory of Edu. For pure Sci. / Ibn al-Haitham in 2016, three boxes for each irradiation dose, each one contain 10 date fruits. Dates. Zahdi variety artificially infested by eggs of Ephestia cautella. Eggs and larvae of insect exposed to different doses of gamma radiation on 5 periods for each dose separated by 5 min for each period of irradiation along with constant dose of UV radiation, 15min for all treated samples. Irradiated dates stored at 19Co for 40 and 30 day for eggs and larvae respectively. Results showed that the mixed radiation technique were effective for eliminating the insect and keeping the dates preserved with high quality A dose of 106Gy and 298Gy of gamma required for 100% of eliminating eggs and larvaes respectively. Physical and chemical characteristics did not changed as a result of irradiation.